Assessing the generality and durability of interview‐informed functional analyses and treatment. Issue 1 (20th September 2018) - Rose, Jordan Chusid; Beaulieu, Lauren
Abstract : Due to the limited research demonstrating socially valid outcomes of function‐based treatments in ecologically relevant environments (Santiago, Hanley, Moore, & Jin, 2016), we replicated and extended the effects of the interview‐informed functional analysis and skill‐based treatment procedure described by Hanley, Jin, Vanselow, and Hanratty (2014) with two children diagnosed with autism in a home setting. The assessment and treatment was implemented by a home‐based service provider and treatment was extended to the participants' parents. Following the interview‐informed functional analyses, we taught the participants functional communication responses and to engage in less‐preferred activities when functional communication outcomes were delayed. We observed large reductions in problem behavior following the introduction of the function‐based treatment. The effects extended to novel settings, stimuli, and caregivers and the results maintained at 6‐week follow‐ups.